Epigraphic Bulletin for Greek Religion 2014 (EBGR 2014) - Chaniōtēs, Angelos (Kernos, 2017)
The 27th issue of the EBGR presents epigraphic corpora and new epigraphic finds published in 2014. I have only included a few contributions to the reading and interpretation of old finds as well as a small selection of publications that adduce inscriptions for the study of religious phenomena. I have also summarizes some publications of 2013 and earlier years that had not been included in earlier issues of the EBGR. This issue presents three corpora: the first part of the corpus of Greek and ...